In vitro and in vivo study of 221Fr and 213Bi progeny release from the 225Ac-labelled TiO2 nanoparticles - Sakmár, Michal; Kozempel, Ján; Kučka, Jan; Janská, Tereza; Štíbr, Matěj; Ondrák, Lukáš; Ondrák Fialová, Kateřina; Vlk, Martin; Šefc, Luděk; Bruchertseifer, Frank; Morgenstern, Alfred (Nuclear medicine and biology, 2025)
BACKGROUND: Targeted alpha therapy (TAT) is an effective option for cancer treatment. To maximize its efficacy and minimize side effects, carriers must deliver radionuclides to target tissues. Most of the nuclides used in TAT decay via the alpha cascade, producing several radioactive daughter nuclei with sufficient energy to escape from the original carrier. Therefore, studying these daughter atoms is crucial in the search for new carriers. Nanoparticles have potential as carriers due to their structure, which can prevent the escape of daughter atoms and reduce radiation exposure to non-target tissues. This work focuses on determining the released activity of 221Fr and 213Bi resulting from the decay of 225Ac labelled TiO2 nanoparticles. RESULTS: Labelling of TiO2 nanoparticles has shown high sorption rates of 225Ac and its progeny, 221Fr and 213Bi, with over 92 % of activities sorbed on the nanoparticle surface for all measured radionuclides. However, in the quasi-dynamic in vitro system, the released activity of 221Fr and 213Bi is strongly dependent on the nanoparticles concentration, ranging from 15 % for a concentration of 1 mg/mL to approximately 50 % for a nanoparticle concentration of 10 μg/mL in saline solution. The released activities of 213Bi were lower, with a maximum value of around 20 % for concentrations of 0.05, 0.025, and 0.01 mg/mL. The leakage of 225Ac and its progeny was tested in various biological matrices. Minimal released activity was measured in saline at around 10 % after 48 h, while the maximum activity was measured in blood serum and plasma at 20 %. The amount of 225Ac released into the media was minimal (<3 %). The in vitro results were confirmed in a healthy mouse model. The difference in %ID/g was clearly visible immediately after dissection and again after 6 h when 213Bi reached equilibrium with 225Ac. CONCLUSION: The study verified the potential release of 225Ac progeny from the labelled TiO2 nanoparticles. Experiments were performed to determine the dependence of released activity on nanoparticle concentration and the biological environment. The results demonstrated the high stability of the prepared 225Ac@TiO2 NPs and the potential release of progeny over time. In vivo studies confirmed our hypothesis. The data obtained suggest that the daughter atoms can escape from the original carrier and follow their own biological pathways in the organism.
Keywords: radionuklidy; tkáňová distribuce; Isotope Labeling; Tissue Distribution; Nanoparticles; titan; nanočástice; Titanium; Actinium-225; Animals; TiO(2); izotopové značení; Targeted alpha therapy; Bismuth-213; zvířata; Radioisotopes; Actinium; myši; aktinium; Mice